2018
DOI: 10.1186/s40360-018-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of free radical scavenging capacity of methoxy containing-hybrids of thiosemicarbazone-triazole and their influence on glucose transport

Abstract: BackgroundDiabetes mellitus is a metabolic disease in which the body is unable to produce insulin or respond to insulin production, consequently leading to abnormal metabolism of carbohydrates, lipids and proteins causing elevation of glucose in the blood. Oxidative stress, an imbalance between the production of free radicals and body antioxidant system has been implicated in the pathogenesis of diabetes. Free radicals attack important macromolecules leading to cell damage. Antioxidants are intimately involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…To our surprise, hexane fraction exhibited an up-regulation glucose uptake relative to standard reference drugs (metformin and glibenclamide). This could be justified by the activation of key transcription factors such as PPARɣ and protein kinase via the inhibition of glycerophosphate dehydrogenase which is also in consonant with what was observed by Ayeleso et al [47] The metabolites responsible may mimic or perform better than metformin widely recognized as the treatment baseline proposed by Rena et al [19] From the results of the chemical profiling of the hexane fraction of the fruit of this study, some important metabolites were detected, identified and confirmed. These compounds are azulene, trans-'a-bergamotene, and 2,4-di-tert-butylphenol which were identified in previous studies as bacterial metabolites, antioxidants and pharmaceuticals [71][72][73] .…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To our surprise, hexane fraction exhibited an up-regulation glucose uptake relative to standard reference drugs (metformin and glibenclamide). This could be justified by the activation of key transcription factors such as PPARɣ and protein kinase via the inhibition of glycerophosphate dehydrogenase which is also in consonant with what was observed by Ayeleso et al [47] The metabolites responsible may mimic or perform better than metformin widely recognized as the treatment baseline proposed by Rena et al [19] From the results of the chemical profiling of the hexane fraction of the fruit of this study, some important metabolites were detected, identified and confirmed. These compounds are azulene, trans-'a-bergamotene, and 2,4-di-tert-butylphenol which were identified in previous studies as bacterial metabolites, antioxidants and pharmaceuticals [71][72][73] .…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 88%
“…In vitro glucose uptake in 3T3 L1 adipocytes 3T3 L1 cells derived from mouse 3T3 cells were fully differentiated after cell culture in glucose-free Dulbecco's modified Eagles medium (DMEM) as confluent monolayers into adipocytes and were exposed to the hexane fraction of Kigelia africana fruit extracts at lower concentrations of 0.05, 0.5, 5 and 50 µg/ml as described by Ayeleso et al [47] Glibenclamide (1 µM) was added as positive control as well as metformin (1 µM) as a reference drug control. The plates were mixed together, sonicated and incubated for 3 h. After the incubation period, glucose uptake in 3T3 L1 adipocytes was determined using pulse labelling with [3H]-2-deoxyglucose (3H-2-DOG) in glucose-free DMEM containing the extract and fractions for 15 min.…”
Section: Instrumentation and Analytical Methodsmentioning
confidence: 99%
“…In contrast, DPPH, a stable nitrogen-centered free radical, is commonly used to measure a compound's ability to either scavenge free radicals or donate hydrogen. 58 H 2 O 2 is freely diffusible, and hence, readily permeates the membrane and damages proteins, nucleic acids, carbohydrates, and lipids. It can give rise to singlet oxygen by reacting with superoxide anion or with HOCl or chloramines.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a multietiological condition characterized by chronic symptoms, 8 due to insu cient insulin hormone production or cells that do not respond to the hormones produced 9 . It is a condition in which the body produces insu cient insulin, stops producing insulin, or becomes increasingly resistant to its activity 10 . In patients with the polygenic condition, effective glucose control is the key to preventing diabetic complications and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%